(untitled) (Sebha University Conference Proceedings, 2025)
Medical applications have become integral components of contemporary healthcare, leveraging advancements in technology to enhance patient care. This paper addresses the need for more efficient communication and decision-making between patients and doctors. The main objective of this research is to develop an AI-based application that serves as an intermediary between the patient and the doctor, streamlining their interactions. The proposed application operates in four phases. First, it collects comprehensive patient data, including test results, x-rays, and self-reported health status, and compiles it into a file stored in a database. Second, the application provides an initial diagnosis based on an AI model and advises whether a doctor’s consultation is necessary. Third, if a consultation is recommended, the system includes the patient’s file and diagnosis in the booking process. Finally, the data is emailed to both the patient and the doctor for reference. The results suggest that this medical application can redefine the doctor-patient relationship by improving communication, providing more consistent interactions, and enhancing diagnostic accuracy.